Pengaruh Carbon Productivity dan Biaya Lingkungan Terhadap Kinerja Keuangan Perusahaan dengan Financial Slacks Sebagai Pemoderasi - Febriani, Dina; Darmawati, Deni (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study aims to test and analyze the effect of carbon productivity and environmental costs on firm financial performance with financial slacks as moderation. The analysis method in this study is multiple linear regression analysis method. The technique used in this study is sample selection with purposive sampling with a total sample of 110 data. The data used is secondary data obtained from the Indonesia Stock Exchange (IDX) with a research population of 88 energy sector companies listed on the IDX during 2021-2023. The results of hypothesis testing in this study indicate that carbon productivity and environmental costs have a positive effect on firm financial performance. Meanwhile, financial slacks as a moderator do not strengthen the relationship between carbon productivity and firm financial performance. But financial slacks as a moderator is able to strengthen the relationship between environmental costs on the firm's financial performance.